Dominant damping effects in friction brake noise, vibration and harshness: the relevance of joints. (May 2015) - Tiedemann, Merten; Kruse, Sebastian; Hoffmann, Norbert
The experimental analysis of a single component of a brake system and an assembly consisting of three components is used to clarify the relevance of joints in terms of damping and non-linearity in state-of-the-art brake systems. For this purpose a series of experimental modal analyses are conducted. A comparison of the results obtained from the single component and from the assembly strongly indicate that the joints which necessarily exist in an assembled structure have a strong impact on the dynamic behaviour of the structure. The modal damping values of the jointed structure are a factor of up to 60 higher than those of the single-component values. Also, a significant amplitude dependence of the frequency response functions results. The observations demonstrate that joints are a major source of energy dissipation in friction brake systems and, in addition, that they introduce non-linear behaviour to the system which has the potential to limit squeal amplitudes. Therefore, mechanical joints in brake systems should be considered as decisive design elements for noise, vibration and harshness issues in brakes.